Potential of Local Microalgae from Lembar Bay Waters for Climate Change Mitigation: Insights from Photosynthetic Assimilation Index - Damai Diniariwisan; Alis Mukhlis; Bagus Dwi Hari Setyono; Awan Dermawan; Rizky Regina Kawirian; Sri Hikmah Wulandari (Journal of Fish Health, 2026)
Climate change mitigation requires innovative approaches to reduce atmospheric carbon dioxide (CO₂) through efficient and sustainable carbon fixation. Microalgae are promising biological agents because of their photosynthetic capacity to assimilate inorganic carbon into biomass. This study aimed to assess the potential of local microalgae communities in Lembar Bay waters, West Lombok, as carbon assimilation agents based on the relationship between chlorophyll-a, net primary productivity (NPP), and assimilation index. The study was conducted from March to May 2026 at five sampling stations, with three sampling periods at 30-day intervals. Phytoplankton samples were collected using a plankton net and identified microscopically, while chlorophyll-a was analyzed spectrophotometrically. NPP was determined using the light-and-dark bottle method based on changes in dissolved oxygen during a six-hour incubation period. The relationships among environmental parameters, chlorophyll-a, and NPP were analyzed using Spearman correlation. The results showed a relatively strong positive correlation between chlorophyll-a and NPP (r = 0.727), indicating that higher phytoplankton biomass was associated with greater photosynthetic productivity. Chlorophyll-a showed weak correlations with nitrate (r = −0.045) and phosphate (r = −0.107). The assimilation index varied among stations, ranging from 6.13 to 11.51 (mg C mg Chl-a⁻¹ hour⁻¹), with the highest value at Station 4 and the lowest at Station 5. These findings indicate that local microalgae in Lembar Bay have potential for biological carbon assimilation and may support climate change mitigation. However, further species-specific cultivation and controlled photobioreactor experiments are required to validate their CO₂ fixation capacity and long-term carbon sequestration potential.